2019
DOI: 10.6018/analesps.35.2.297741
|View full text |Cite
|
Sign up to set email alerts
|

The revolving door to homelessness. The influence of health, alcohol consumption and stressful life events on the number of episodes of homelessness.

Abstract: Objectives.- To analyse the impact of different variables on repeated episodes of homelessness. Method.- The study was conducted based on data obtained from a representative sample of homeless people in Madrid (Spain) (n = 188). Results.- Suffering from a serious or chronic illness has an effect on the revolving door to homelessness, which is mediated by a highly negative subjective perception of the individual's own health, which is in turn mediated by suffering from a disability. Excessive alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 18 publications
1
34
0
7
Order By: Relevance
“…However, contrary to the observations by other authors (Christensen & Vinther, 2005), the phenomenon of the "revolving door to homelessness" seems to affect women to a greater extent in Madrid. Many circumstances may lead individuals to suffer from repeated episodes of homelessness after gaining access to independent housing, although issues related to health, excessive alcohol consumption and experiencing stressful life events appear to be particularly influential (Aubry, Klodawsky, & Coulombe, 2012; Caton et al, 2005; Dworsky, Napolitano, & Courtney, 2013; Greenberg & Rosenheck, 2010; Kim, Kertesz, Horton, Tibbetts, & Samet, 2006; Muñoz et al, 2004; Parker, 2010, Roca et al, 2019). There are various explanations for homeless women in Madrid becoming homeless on more occasions than men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, contrary to the observations by other authors (Christensen & Vinther, 2005), the phenomenon of the "revolving door to homelessness" seems to affect women to a greater extent in Madrid. Many circumstances may lead individuals to suffer from repeated episodes of homelessness after gaining access to independent housing, although issues related to health, excessive alcohol consumption and experiencing stressful life events appear to be particularly influential (Aubry, Klodawsky, & Coulombe, 2012; Caton et al, 2005; Dworsky, Napolitano, & Courtney, 2013; Greenberg & Rosenheck, 2010; Kim, Kertesz, Horton, Tibbetts, & Samet, 2006; Muñoz et al, 2004; Parker, 2010, Roca et al, 2019). There are various explanations for homeless women in Madrid becoming homeless on more occasions than men.…”
Section: Discussionmentioning
confidence: 99%
“…There are various explanations for homeless women in Madrid becoming homeless on more occasions than men. According to the model proposed by Roca et al (2019), suffering from serious or chronic illness (observed to a greater extent among women) has a negative effect on the "revolving door to homelessness," mediated by a negative perception of one’s own health, which is in turn mediated by suffering from disability. Homeless women with a serious illness and/or a disability may have a limited ability to function, which leads to increased care needs and greater dependence on others (Parker, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SLEs are defined as experiences that play a key role in people's lives and that involve significant life changes. According to different studies, experiencing severe and multiple SLEs is a vulnerability factor for becoming homeless (Toro & Oko-Riebau, 2015;Zugazaga, 2004), but at the same time, SLEs influence homelessness chronification by increasing the "revolving door to homelessness" (i.e., the return to homelessness after access to independent housing; Roca et al, 2019).…”
Section: Introductionmentioning
confidence: 99%